2017
DOI: 10.1186/s12967-017-1166-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MRI and ex vivo histological assessment of the cardioprotection induced by ischemic preconditioning, postconditioning and remote conditioning in a closed-chest porcine model of reperfused acute myocardial infarction: importance of microvasculature

Abstract: BackgroundCardioprotective value of ischemic post- (IPostC), remote (RIC) conditioning in acute myocardial infarction (AMI) is unclear in clinical trials. To evaluate cardioprotection, most translational animal studies and clinical trials utilize necrotic tissue referred to the area at risk (AAR) by magnetic resonance imaging (MRI). However, determination of AAR by MRI‚ may not be accurate, since MRI-indices of microvascular damage, i.e., myocardial edema and microvascular obstruction (MVO), may be affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 70 publications
(94 reference statements)
4
47
1
Order By: Relevance
“…This trend is consistent with data from the literature. Indeed, ischemic preconditioning could be responsible for vascular collateralisation, improving the myocardium perfusion [30]. While hs-TnT first peak correlated with the infarct size, it did not reflect the quality of the reperfusion in our study.…”
Section: Hs-tnt and Myocardial Infarction Characteristicscontrasting
confidence: 68%
“…This trend is consistent with data from the literature. Indeed, ischemic preconditioning could be responsible for vascular collateralisation, improving the myocardium perfusion [30]. While hs-TnT first peak correlated with the infarct size, it did not reflect the quality of the reperfusion in our study.…”
Section: Hs-tnt and Myocardial Infarction Characteristicscontrasting
confidence: 68%
“…However, none of the trials were pre-specified for this endpoint. Nonetheless, a subsequent study in pigs found that RIC attenuated the extent of myocardial edema as measured by T2-weighted CMR 168 . Evaluation of MaR through T2-weighted and T2-mapping as well as early contrast-enhanced steady state free precession CMR sequences are edemabased and it has therefore been suggested that intervention with RIC may reduce the extent of edema and thereby MaR determined with CMR 169,170 .…”
mentioning
confidence: 96%
“…Therefore, it is important to investigate MVO in preclinical studies, to gather information for a better understanding of the pathomechanism and to find possible therapeutic options. In a large animal model, late gadolinium-enhanced cardiac MRI was used to assess the myocardial MVO burden after different ischemic conditionings [ 50 ]. So far, several findings have shown that myocardial edema and MVO are altered independently of myocardial necrosis, which is in line with the findings of clinical trials [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large animal model, late gadolinium-enhanced cardiac MRI was used to assess the myocardial MVO burden after different ischemic conditionings [ 50 ]. So far, several findings have shown that myocardial edema and MVO are altered independently of myocardial necrosis, which is in line with the findings of clinical trials [ 50 ]. In the present model, we used thioflavine-S staining perfused through the whole heart and the heart slices were investigated under UV light to visualize the penetration of the dye into the tissue.…”
Section: Discussionmentioning
confidence: 99%